Elevation in fibroblast growth factor 23 and its value for identifying subclinical atherosclerosis in first-degree relatives of patients with diabetes - Hu, Xiang (Sci Rep, 2016)
Accumulating evidence supported an association between diabetes and fibroblast growth factor 23 (FGF23). The goal of the present study was to explore alteration in serum FGF23 levels and to assess its value for identifying subclinical atherosclerosis in normoglycemic individuals with a first-degree family history of diabetes (FHD). The study enrolled 312 subjects with a first-degree FHD and 1407 subjects without an FHD. Serum FGF23 levels were detected by a sandwich enzyme-linked immunosorbent assay. Serum FGF23 levels were much higher in subjects with a first-degree FHD than in those without an FHD (P = 0.006). A first-degree FHD was positively associated with serum FGF23 levels, independent of C-IMT and cardiovascular factors (both P < 0.05). In subjects with a first-degree FHD, only those with serum FGF23 levels in the upper quartile were more likely to have an increased C-IMT (odds ratio = 2.263, P < 0.05). As conclusions, a first-degree FHD contributes to the increased serum FGF23 levels independently. Subjects with a first-degree FHD need higher serum FGF23 levels to indicate subclinical atherosclerosis. The influence of a first-degree FHD on serum FGF23 levels should be considered to avoid overestimating the risk of cardiovascular disease in normoglycemic individuals with a first-degree FHD.